Research on construction materials of the Witwatersrand region - Blight, Geoffrey Eustace (My University, 1985)
This volume contains a record of research carried out over the past two decades into problems associated with civil engineering and mining construction materials. Although the various parts of the work were initiated as a result of problems that arose in the Witwatersrand region, the results of the research have in many cases evoked intense interest from other parts of the world. For example, the work on soluble salts in road bases has been taken up in Saudi Arabia and other desert regions, while that on the stability of waste rock dumps has been adopted as a basis for rock dump design in the United States of America. The research revolves entirely about materials, usually, waste, either produced by the mines and reused or disposed of by civil engineers; or reused to provide support by the mines · themselves. The main aim and end result of the research has been a more effective and efficient use of materials and better protection and control of the local environment.
A thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy in Science to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, Johannesburg, 1985
Keywords: The disposal of mine waste; The use of mine waste as a construction material; The provision Of underground support; Environmental problems associated with mine waste; Geotechnical Problems Of The Witwatersrand.